Brevifoliol ester induces apoptosis in prostate cancer cells by activation of caspase pathway. (20th October 2019) - Bhukya, Balakishan; Fatima, Kaneez; Nagar, Abhishek; Lakshmi, Vijaya; Dubey, Poornima; Kumar, Shailesh; Kumar, Yogesh; Luqman, Suaib; Chanda, Debabrata; Tandon, Sudeep; Shanker, Karuna; Khan, Feroz; et al.
Abstract: Prostate cancer is fourth most abundant cancer type around the globe. Brevifoliol, a rearranged taxoid from Taxus walllichiana needles has been derivatized as C5 esters using Steglich esterification reaction. Seventeen diverse analogues were evaluated against a panel of human cancer cell lines by MTT assay. Among these, two of the semi‐synthetic analogues, that is, 13 and 16 exhibited potent cytotoxicity, selectively against PC‐3, prostate cancer cell lines. In cell cycle analysis, analogue 13 induced S and G2/M phase arrest and induced apoptosis by activating caspase‐3. Compound 13 showed moderate efficacy in in‐vivo Ehrlich ascites carcinoma in Swiss albino mice. Further, compound 13 was found to be safe in Swiss albino mice up to 1, 000 mg/kg dose in acute oral toxicity. Brevifoliol ester 13 may further be optimized for better efficacy. Abstract : Synthesis and biological evaluation of C5 esters of brevifoliol, a rearranged taxoid.